Programa "Minha Casa, Minha Vida": política habitacional ou pacote anticíclico - Mara Cristina Nogueira Teixeira (2012)
The aim of this study is to present an analysis of Minha Casa, Minha Vida, a housing program launched in March 2009 by Lulas administration with the purpose of building one million houses in two years for families with income up to ten minimum wages. The program clearly has a double intention: to reduce Brazilian housing deficit and to generate income and employment through investments on the construction activity. Considering the distinct character of PMCMVs alleged aims, the present analysis will also be divided into two different parts. In the first paper it was measured the impacts of the program in the employment volume of Brazilian municipalities. The study was based on the keynesian principle of effective demand and it has used the Generalized Propensity Score methodology. The results point to positive and significant effects of the program, especially in small cities and low-skilled, low-paying occupations. In the second study it was realized an analysis of PMCMVs impacts on the housing deficit. According to the examined data, the proposed regional division of the constructions was not followed. Besides that, after a year, the program had delivered far less units than initially promised, notably for the lower wage range. It was also analyzed the quality, in terms of basic urban infra-structure services and surroundings, of the benefited areas at Belo Horizonte, Rio de Janeiro and São Paulo. For this purpose, it was used data of 2010 Census and PMCMVs funding, explored using Multiple Correspondence Analysis, a multivariate statistical technique. There is a slight tendency towards a better location to the constructions for the higher wage ranges. However, in the average, the houses are being built on regions with median quality, next to ideal. The two studies ensemble, point out that the PMCMV has better accomplished its countercyclical purposes and despite some advances, as a housing program it still remains little encompassing.